Clinical Resistome Screening of 1,110 Escherichia coli Isolates Efficiently Recovers Diagnostically Relevant Antibiotic Resistance Biomarkers and Potential Novel Resistance Mechanisms - Volz, Carsten; Ramoni, Jonas; Beisken, Stephan; Galata, Valentina; Keller, Andreas; Plum, Achim; Posch, Andreas E.; Müller, Rolf (Frontiers in Microbiology, 2019)
Multidrug resistant pathogens represent one of the biggest global healthcare challenges. Molecular diagnostics can guide effective antibiotics therapy but depends on validated, predictive biomarkers. We here present a novel, generically applicable workflow for rapid identification of antimicrobial resistance (AMR) biomarkers from clinical E. coli isolates and quantitatively evaluate the potential to recover causal biomarkers for observed resistance phenotypes. For this, a metagenomic plasmid library from 1,110 clinical E. coli isolates was created and used for high-throughput screening to identify biomarker candidates against Tobramycin, Ciprofloxacin and Trimethoprim-Sulfamethoxazole. Identified candidates were further validated in-vitro and also evaluated in-silico for their diagnostic performance based on matched genotype-phenotype data. AMR biomarkers recovered by the metagenomics screening approach mechanistically explained 77% of observed resistance phenotypes for Tobramycin, 76% for Trimethoprim-Sulfamethoxazole and 20% Ciprofloxacin. Sensitivity for Ciprofloxacin resistance detection could be improved to 97% by complementing results with AMR biomarkers that are undiscoverable due to intrinsic limitations of the workflow. Additionally, when combined in a multiplex diagnostic in-silico panel, the identified AMR biomarkers reached promising positive and negative predictive values of up to 97% and 99%, respectively. Finally, we demonstrate that the developed workflow can be used to identify potential novel resistance mechanisms.